Assertive Speech Acts in Donald Trump’s Presidential Speeches - Kartika Dina Ashfira; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2020)
This research investigates assertive speech acts in Donald Trump’s presidential speeches. It classifies the assertive speech acts based on their illocutionary forces according to Bach and Harnish (1979). The data were taken from three speeches by Donald Trump. The results show that the illocutionary forces of assertive speech acts found in the speeches are affirming, alleging, asserting, avowing, claiming, declaring, denying, maintaining, propounding, saying, and stating. The act of stating is the most commonly used (44%). The findings suggest that Trump uses the act of stating mostly because he wants the hearer to believe him that the policies he has made are the best for the United States.